(untitled) (Journal of the Management Sciences, 2025)
This study examines the relationship between strategic integration of green human capital development (GHCD) and employee innovativeness in the context of global food retail supply chains with selected Spar retail outlets in Lagos State as a case study. The research focuses on the roles of green performance management and appraisal and green compensation and rewards in fostering employee innovativeness. A quantitative research design was adopted, utilizing a survey method with a structured questionnaire. The study’s population consisted of 122 employees of selected Spar retail outlets. Using the Taro Yamane (2004) sample size model, a sample size of 93 was determined. Data was collected via convenience sampling technique. The result of the hypothesis one shows t-value is 5.279, and the p-value (Sig.) is 0.000, which is highly significant (p < 0.05). The unstandardized coefficient of hypothesis two which is 0.687 with a standard error of 0.089, and a t-value of 7.680 with the corresponding p-value is 0.000, which is less than 0.05. This indicates that the relationship of the two hypotheses tested are statistically significant. The study concludes that green human capital development proxy with green performance management and appraisal and green compensation and rewards has significant relationship with employees’ innovativeness. The findings provide practical recommendations for retail outlets to formally integrate green performance indicators into the standard performance management and appraisal systems for all employees by ensuring that objectives related to energy conservation, waste reduction, recycling initiatives, and resource efficiency are clearly defined, measurable, and weighted in the appraisal process.